Wetland Dynamics, Trends and Environmental Implications: Comparative Study in Bamenda II and III Municipalities, North West Region, Cameroon - Mbanga Lawrence Akei; Dingha Chrispo Babila (Coğrafya Dergisi)
Despite the loss of wetlands at varying degrees around the world, there is insufficient empirical information to elucidate the trajectories in wetland dynamics, especially in developing countries. As such, this study examines the trends in wetlands dynamics in the Bamenda II and III municipalities of Cameroon, analyzes the environmental implications, and investigates some adaptation and mitigation strategies to wetlands mutation seen in these areas. Data was collected from institutions and online sources, and supported by interviews, field surveys, and the administration of a questionnaire to 164 respondents. Satellite images were downloaded from USGS for 1980, 2000 and 2020. These were corrected, and processed in ArcGIS 10.3 using the interactive supervised classification tool and converted from raster to vector, permitting the production of LULC maps and automatic calculation of changes in wetland areas. Frequency and descriptive analyses was done in SPSS version 20 and Microsoft Excel 2016. The results indicate that wetlands decreased from 33.91 km2 to 28.58 km2 in Bamenda II and from 13.58 km2 to 9.09 km2 in Bamenda III from 1980 to 2020. This retreat of wetlands is associated with biodiversity loss, pollution and flooding, which are the basis for engineering and non-engineering adaptation measures.